Corrections to ’’Minimal piecewise linear cones in R^4’’ (Math. Scand. 130 (2024), 149–160) - Valfells, Ásgeir (MATHEMATICA SCANDINAVICA, 2025)
The paper “Minimal piecewise linear cones in R^4” (Math. Scand. 130 (2024), 149–160) contains two errors. The result is weakened from a full classification of the five minimal piecewise linear cones in R^4 to a classification of five minimizers and two candidates that we could not determine whether were minimizing or not.